Perioperative and anesthesia-related mortality: An 8-year observational survey from a tertiary teaching hospital - Pignaton, Wangles [UNESP]; Braz, José Reinaldo C. [UNESP]; Kusano, Priscila S. [UNESP]; Módolo, Marília P. [UNESP]; De Carvalho, Lídia R. [UNESP]; Braz, Mariana Gobbo [UNESP]; Braz, Leandro Gobbo [UNESP] (Wolters Kluwer, 2016)
In 2006, a previous study at our institution reported high perioperative and anesthesia-related mortality rates of 21.97 and 1.12 per 10,000 anesthetics, respectively. Since then, changes in surgical practices may have decreased these rates. However, the actual perioperative and anesthesia-related mortality rates in Brazil remains unknown. The study aimed to reexamine perioperative and anesthesia-related mortality rates in one Brazilian tertiary teaching hospital. In this observational study, deaths occurring in the operation room and postanesthesia care unit between April 2005 and December 2012 were identified from an anesthesia database. The data included patient characteristics, surgical procedures, American Society of Anesthesiologists (ASA) physical status, and medical specialty teams, as well as the types of surgery and anesthesia. All deaths were reviewed and grouped by into 1 of 4 triggering factors groups: totally anesthesia-related, partially anesthesia-related, surgery-related, or disease/conditionrelated. The mortality rates are expressed per 10,000 anesthetics with 95% confidence intervals (CIs). A total of 55,002 anesthetics and 88 deaths were reviewed, representing an overall mortality rate of 16.0 per 10,000 anesthetics (95% CI: 13.0-19.7). There were no anesthesia-related deaths. The major causes of mortality were patient disease/condition-related (13.8, 95% CI: 10.7-16.9) followed by surgery-related (2.2, 95% CI: 1.0-3.4). The major risks of perioperative mortality were children younger than 1-year-old, older patients, patients with poor ASA physical status (III-V), emergency, cardiac or vascular surgeries, and multiple surgeries performed under the same anesthetic technique (P < 0.0001). There were no anesthesia-related deaths. However, the high mortality rate caused by the poor physical conditions of some patients suggests that primary prevention might be the key to reducing perioperative mortality. These findings demonstrate the need to improve medical perioperative practices for high-risk patients in under-resourced settings.